The corporatisation of local body entities: A study of financial performance - Hooks, J. J.; van Staden, C. J. (Massey University, 2003)
The New Zealand electricity industry provides us with a unique opportunity to examine how entities responded to major restructuring of the industry. This research studies the financial performance of three entities, each with a different ownership structure, over a 15 year period from 1988 to 2002. The aim is to examine the possible influence of ownership type and corporatisation on the development and financial performance of the entities by examining the changes that took place from the pre-corporatisation period to the post-corporatisation period and comparing and contrasting the performance and funding of the three entities over that time. In this way an assessment is made of the possible influence of ownership type on financial performance. This research can be framed to some extent by agency theory aspects of positive accounting theory. In addition legitimacy theory has been used to explain the behaviour of managers and the process of organizations adapting to a changing environment. Both theories acknowledge the interaction of organizations and their environment. The comparison shows that at the end of the study period the council owned company was the smallest, in terms of total assets, of the three companies examined (although it was similar in size to the biggest one at the outset). The council owned company also returned most capital to its shareholders and is the most conservatively financed one of the three with only 10% debt at the end of 2002 compared to 28% for the trust-held company and 87% for the listed company. The listed company ended up being the biggest and the one with the highest gearing, the highest ROA and the highest profit margin. The study concludes that ownership structure did have an influence on financial performance and level of debt funding.
Keywords: Electricity company accounting; Restructuring; Organisational change